Visible-light-driven AgBr–TiO2-Palygorskite photocatalyst with excellent photocatalytic activity for tetracycline hydrochloride. (20th December 2020) - Shi, Yingying; Yan, Zhuan; Xu, Yingtao; Tian, Tian; Zhang, Jing; Pang, Jianfeng; Peng, Xihua; Zhang, Qianghua; Shao, Mingli; Tan, Wenyi; Li, Hailun; Xiong, Qingping
Abstract: Tetracycline hydrochloride (TC) wastewater has complex components, high concentration of organic matter and certain biological toxicity. Photocatalytic degradation is of great application prospect due to its green, thorough and efficient removal of TC. In this study, heterojunction photocatalyst supported on Palygorskite (Pal) AgBr–TiO2 -Pal with visible light response was successfully prepared via sol-gel and liquid deposition method successfully. Taking TC as the target pollutant, the photocatalytic performance of AgBr–TiO2 -Pal photocatalys excited by visible light was studied. The spreading/grafting of AgBr–TiO2 on the surface of Pal was improved by a series of structural characterization and composition analysis. The results also demonstrated that the specific surface area of AgBr–TiO2 -Pal was about 48.06 m 2 ⋅g −1 with uniform mesoporous slit. The AgBr–TiO2 -Pal catalyst was very effective for the degradation of TC, and it still retained its high stability and reusability after five cycles. The results showed that under the best reaction conditions (initial concentration of tetracycline 10 mg⋅L −1, catalyst dosage 0.5 g⋅L −1, pH value 9), with the excitation of visible light, the maximum removal ratio of TC was 90%, and the mineralization ratio was 67%. The removal efficiency and degradation rate of TC by AgBr–TiO2 -Pal catalyst were 2.17 and 4.75 times as much as those of TiO2 respectively. The outstanding photocatalytic performance of heterogeneous AgBr–TiO2 -Pal catalyst was obtained by fully participate in the reaction by photoinduced charge. This study could be expected to be used in photocatalytic degradation of antibiotic pollutants in wastewater treatment. Highlights: A novel AgBr–TiO2 -Pal photocatalyst is prepared for tetracycline degradation. The catalyst support, Palygorskite, has a porous structure and large surface area. The AgBr–TiO2 heterostructure has enhanced visible light photocatalytic activity. The catalyst can be recycled more than five times by a simply filtered.